1998
DOI: 10.1046/j.1365-2648.1998.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and quality of life among patients on continuous ambulatory peritoneal dialysis (CAPD)

Abstract: The present study describes CAPD patients' coping strategies and quality of life. A descriptive-comparative design was chosen and a consecutive series of patients (n = 26) was included. Data collection was performed through questionnaire and interview. Coping was measured by the Jalowiec Coping Scale and quality of life by the Swedish Health-Related Quality of Life Survey (SWED-QUAL). The main results show that an optimistic coping style was the most widely used by both men and women and this style was also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
41
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 15 publications
10
41
1
Order By: Relevance
“…However, for those on peritoneal dialysis, the optimistic style was more common. (30) A study with patients on peritoneal dialysis found a higher prevalence of the optimistic style, followed by self-reliant, (30) similar to the results of the present study where self-reliant was followed by optimistic, in both focuses and emotion.…”
Section: Discussionsupporting
confidence: 89%
“…However, for those on peritoneal dialysis, the optimistic style was more common. (30) A study with patients on peritoneal dialysis found a higher prevalence of the optimistic style, followed by self-reliant, (30) similar to the results of the present study where self-reliant was followed by optimistic, in both focuses and emotion.…”
Section: Discussionsupporting
confidence: 89%
“…They have one thought: recover their normal life and be a normal person, again. They wish to be independent and normal (4)(5) . Some studies described the patients' need to look and feel more healthy and more like other people despite the disease and long term treatment (7)(8)11,20) .…”
Section: Comprehensive Understandingmentioning
confidence: 99%
“…The specific self-management activities done by patients include performing dialysis procedures; caring for catheter and exit site*; taking medications; following diet and fluid limits; and conducting self-assessment, including observation for complications (3) . In this process, nurses have an educational role: they prepare the patients and relatives to carry out procedures of dialysis at home, encouraging patients to take over their own care supported by their family (4)(5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…The life quality level of dialysis treated patients is lower than the other people in society (Lindqvist and Sjoden, 1998). The chronic and weakening nature of disease, the long-lasting and dynamic therapy and patients' actual and potential problems (Rahimi et al, 2006) show their need to support (Tayyebi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%